STRATEGI PENGEMBANGAN USAHA MELALUI BUSINESS MODEL CANVAS UD. JAYANTI - Fittrotun Nur Afidah; Hadi Ismanto (CV. Denasya Smart Publisher, 2025)
This research aims to analyze UD's business development strategy. Jayanti through the Business Model Canvas (BMC) approach. UD. Jayanti is a Micro and Small Industry (IMK) which operates in the field of household equipment production, experiencing problems with shortages of raw material stock for cake brush strings, direct selling promotions, and sales through agents and not through customers. The method used is qualitative with a phenomenological approach, with data collection techniques in the form of interviews, observation and recording. The focus of this research is on three elements of BMC, namely Customer Segment, Customer Relationship, and Key Partner. Customer Segment Analysis is to group customers based on characteristics and behavior which focuses on UD problems. Jayanti sells directly through non-customer agents. Customer Relationship is a company interaction strategy with customers to build mutually beneficial relationships which focus on UD problems. Jayanti promotes direct selling, and Key Partner Elements, namely parties who collaborate with the company who focus on UD problems. Jayanti is short of stock of raw materials for cake brush strings. UD. Jayanti also implements business development strategies, namely product strategy, price strategy, location strategy and promotion strategy. The research results show that the product strategy, namely UD. Jayanti produces various household appliances that must remain relevant by understanding consumer characteristics and preferences which can increase customer satisfaction. Pricing strategy by implementing flexible prices, for example by providing discounts for large purchases or loyalty programs for regular customers. The location strategy is UD. Jayanti needs to ensure that products are easily accessible to customers by utilizing online platforms for sales. Promotional strategies, namely collaboration with influencers or local media, can help introduce products to a wider audience.